Thrombotic Microangiopathy and acute kidney injury with malaria: One-year experience at SIUT - Zaidi, Syeda Qurat ul Ain; Naqvi, Rubina (Pakistan Journal of Kidney Diseases, 2024)
Acute Kidney Injury (AKI) may occur with malarial infection, falciparum and vivax species. AKI, anemia, jaundice and thrombocytopenia are documented associated findings. Thrombotic Microangiopathy (TMA) in relation with malarial AKI is less reported subject. Patients and Methods: Between January 2023 to December 2023, patients with diagnosis of malaria and developing AKI (according to KDOQI guidelines definition), who were brought to our institute, showing some clinical and basic laboratory features of TMA or shown delayed recovery were subjected to renal biopsy. Only those where histological diagnosis of TMA was confirmed were included in present study. Results: During last calendar year 17 adult patients fulfilled criteria of malaria, AKI and TMA, of these 15 (88%) were female. Malaria was caused by vivax species in 15 (88%), falciparum in one and one patient who arrived late here had report of malarial parasite seen in private laboratory, species was not mentioned. All had febrile illness, associated symptoms were oligo-anuria in 15(88%), vomiting 13 (76%), body aches 12(70%), and jaundice in 6 (35%). The mean age was 26.58±8.9 years, hemoglobin 7.84±1.78, urea 162.70±67.94, creatinine 8.06±4.69 and LDH 1434.05±925.36. Hemodialysis was required in 16 (94%) patients. After getting biopsy results plasma exchanges done in 15 (88%) patients. Complete recovery of renal function seen in 6 (35%), CKD in 7 (41%). Conclusion: TMA in association with malarial AKI is less reported in literature. Vivax malaria has shown devastating complications with this previously labelled “benign” species of plasmodium.